Entrepreneurship culture: Aggregate trait or collective programming of the mind? - Michael Stützer (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2023)
The answer is yes to both. For decades, research on entrepreneurship culture has relied on two competing theoretical foundations for the important concept of entrepreneurship culture. One camp views entrepreneurship culture as an aggregate of personality traits conducive for entrepreneurship. The other camp applies Hofstede's (1980) definition of culture as 'collective programming of the mind' towards entrepreneurship (e.g., Beugelsdijk, 2007, Hofstede et al., 2004; Stephan and Uhlander, 2010). In this paper I present empirical evidence that measures of entrepreneurship culture reflecting both approaches explain entrepreneurial intentions and action. Entrepreneurship culture is thus both - an aggregate personality trait and a collective programming of the mind.
Keywords: 330